Riding Mozilla's Firefox and the real cost of Linux. (Architects' Journal, 2004)
Presents views of the author on the performance of Mozilla Firefox, a non-Internet Explorer browser, and the cost of Linux version 10. Similarity of the performance of Firefox with Internet Explorer; Inability of Linux to recognize the computer hardware; Cost of the software.